LEGAL REASONING OF THE JUDGE'S DECISION REGARDING GOVERNMENT PROCUREMENT CONTRACT GUARANTEE CLAIM - A Malik, Djamil; Erwin, Yulias; Nurjannah Septyanun (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The decision is a written legal text made by an authorized judge, and its legal product is categorized as a crown. However, despite being considered a crown, a judge's decision is not exempt from examination by legal scholars. The optics used in the examination process are based on various perspectives, including hermeneutics as the fundamental basis for interpreting the text (decision). Substantively, hermeneutics has three main streams of thought, namely as a theoretical (methodological), philosophical, and critical hermeneutics, each with different understandings. Hermeneutics as a method focuses more on the effort to capture and reveal the meaning of the text, while philosophical hermeneutics goes beyond that and emphasizes